Climate Literacy – New or Derived Literacy? - Scholzová, Veronika; Janoušková, Svatava (Scientia in educatione, 2024)
In conjunction with various adjectives, literacy has become commonly used in pedagogical and lay vocabulary. Thanks to the PISA survey, we use terms like mathematical, science, and financial literacy. These terms continue to grow (e.g., environmental and digital literacy). For most of them, there has yet to be a consensus on a precise definition. In our theoretical study, we analyze the concepts of science, environmental, and climate literacy. Based on this analysis, we conclude that the current definition of climate literacy does not introduce any new dimension other than those already included in science and environmental literacy. Therefore, it is redundant for school practice and, to some extent, also for research. A good knowledge of long-standing science and environmental literacies will enable teachers to grasp derived literacies, including climate literacy or literacy related to sustainability.